Usability Evaluation of the Online Marriage Registration Feature in SIMKAH - Dzatama, Krisna Fahrizal; Erna Daniati; Anita Sari Wardani (Information Technology and Science (ITScience), 2025)
The development of digital technology has encouraged government agencies to adopt online-based public services. One such system is SIMKAH (Marriage Management Information System), a web-based platform initiated by the Indonesian Ministry of Religious Affairs to simplify marriage registration processes at Kantor Urusan Agama (KUA). However, several usability challenges remain, particularly in its online registration feature. This study aims to evaluate the usability of SIMKAH using the Think Aloud method based on ISO 9241-11, focusing on effectiveness, efficiency, and satisfaction aspects. The study involved 10 participants, all prospective brides and grooms who had never used SIMKAH before. They were asked to complete 10 scenario-based tasks while verbalizing their thoughts. The results show a high effectiveness rate of 87%, indicating that users were generally able to complete tasks successfully. However, efficiency was affected by lengthy form fields and confusing file upload sections. Satisfaction received a score of 4.1 out of 5, reflecting a positive experience overall, although users noted a lack of clear guidance, feedback notifications, and mobile optimization. User feedback highlighted the need for interface improvements, such as simplifying form structures, adding real-time validation, implementing autosave features, and enhancing visual guidance. These findings suggest that while SIMKAH is functionally adequate, improvements in usability are crucial to ensure a more seamless and satisfying user experience in digital public services